2010
DOI: 10.1007/s00125-010-1935-1
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes-induced peroxynitrite impairs the balance of pro-nerve growth factor and nerve growth factor, and causes neurovascular injury

Abstract: Aims/hypothesis Diabetic retinopathy, the leading cause of blindness in working-age Americans, is characterised by reduced neurotrophic support and increased proinflammatory cytokines, resulting in neurotoxicity and vascular permeability. We sought to elucidate how oxidative stress impairs homeostasis of nerve growth factor (NGF) and its precursor, proform of NGF (proNGF), to cause neurovascular dysfunction in the eye of diabetic patients. Methods Levels of NGF and proNGF were examined in samples from human pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
132
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(149 citation statements)
references
References 45 publications
15
132
0
Order By: Relevance
“…2a, diabetes induced glial activation as indicated in the filaments of Müller cells by prominent GFAP immunoreactivity extending from the nerve fibre layer and inner plexiform layer into the outer nuclear layer of retina, as compared with controls. Recent studies have identified Müller cells as a major site of proNGF expression in the retina [10,25]. Consistent with this, diabetic retinas showed prominent immunolocalisation of proNGF in Müller cells and inner retinal layers, as indicated by prominent colocalisation of proNGF and GFAP, a marker of Muller activation (Fig.…”
Section: Epicatechin Prevents Diabetes-induced Neuronal Cell Deathsupporting
confidence: 77%
See 2 more Smart Citations
“…2a, diabetes induced glial activation as indicated in the filaments of Müller cells by prominent GFAP immunoreactivity extending from the nerve fibre layer and inner plexiform layer into the outer nuclear layer of retina, as compared with controls. Recent studies have identified Müller cells as a major site of proNGF expression in the retina [10,25]. Consistent with this, diabetic retinas showed prominent immunolocalisation of proNGF in Müller cells and inner retinal layers, as indicated by prominent colocalisation of proNGF and GFAP, a marker of Muller activation (Fig.…”
Section: Epicatechin Prevents Diabetes-induced Neuronal Cell Deathsupporting
confidence: 77%
“…We and others have demonstrated increases in expression of nerve growth factor (NGF) in experimental models of diabetes and in clinical diabetes [7][8][9]. Recent findings by our group showed that diabetes-induced peroxynitrite formation impairs cleavage and maturation of NGF, leading to accumulation of its precursor 'proNGF' at the expense of the mature NGF levels, both in experimental models and in clinical diabetes [10]. Accumulation of proNGF after injury has been detected in several neurodegenerative diseases, such as Alzheimer's, [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…827 828 829 830 831 832 833 834 835 836 837 838 839 840 841 842 843 844 845 846 847 848 849 850 851 852 853 854 855 856 857 858 859 860 861 862 863 864 865 866 867 868 869 870 871 872 873 874 875 876 877 878 879 880 881 882 883 884 885 Elevated levels of peroxynitrites have been recently associated to an increased RhoA activity, largely responsible for vascular dysfunction in experimental diabetes [231]. On the same line, diabetesinduced endothelial aortic dysfunction is improved in ROCK knockout mice [232].…”
Section: Rock (Rho-associated Kinase) Inhibitors -mentioning
confidence: 99%
“…The levels of brain-derived neurotrophic factor (BDNF) [7] and nerve growth factor (NGF) [30] are both decreased in the diabetic retina. NGF is produced from pro-NGF by the proteolytic activity of matrix metalloproteinase (MMP)-7.…”
Section: Neuroinflammatory Signaling and Cellular Disorders In The Rementioning
confidence: 99%